2008
DOI: 10.1029/2008gl035584
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and longitudinal dependence of equatorial disturbance vertical plasma drifts

Abstract: [1] We used equatorial measurements from the ROCSAT-1 satellite to determine the seasonal and longitudinal dependent equatorial F region disturbance vertical plasma drifts. Following sudden increases in geomagnetic activity, the prompt penetration vertical drifts are upward during the day and downward at night, and have strong local time dependence at all seasons. The largest prompt penetration drifts near dusk and dawn occur during June solstice. The daytime disturbance dynamo drifts are small at all seasons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
261
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(305 citation statements)
references
References 25 publications
44
261
0
Order By: Relevance
“…Dynamic interactions between the solar wind and the magnetosphere are the source of the magnetospheric dynamo. This gives rise to electrical currents which, along with their associated electric fields [called penetrating interplanetary electric fields (IEFs)], can penetrate to lower latitudes through the conducting ionosphere (Fejer and Scherliess 1995;Fejer et al 2008;Huang et al 2007;Zhao et al 2008). The second mechanism is instead generated by an energy input to the thermosphere that alters the global thermospheric circulation, modifying the electric fields and currents that are generated by the ionospheric wind dynamo action during quiet conditions at low and mid-latitudes (Fejer et al 2008;Nicolls et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic interactions between the solar wind and the magnetosphere are the source of the magnetospheric dynamo. This gives rise to electrical currents which, along with their associated electric fields [called penetrating interplanetary electric fields (IEFs)], can penetrate to lower latitudes through the conducting ionosphere (Fejer and Scherliess 1995;Fejer et al 2008;Huang et al 2007;Zhao et al 2008). The second mechanism is instead generated by an energy input to the thermosphere that alters the global thermospheric circulation, modifying the electric fields and currents that are generated by the ionospheric wind dynamo action during quiet conditions at low and mid-latitudes (Fejer et al 2008;Nicolls et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…This gives rise to electrical currents which, along with their associated electric fields [called penetrating interplanetary electric fields (IEFs)], can penetrate to lower latitudes through the conducting ionosphere (Fejer and Scherliess 1995;Fejer et al 2008;Huang et al 2007;Zhao et al 2008). The second mechanism is instead generated by an energy input to the thermosphere that alters the global thermospheric circulation, modifying the electric fields and currents that are generated by the ionospheric wind dynamo action during quiet conditions at low and mid-latitudes (Fejer et al 2008;Nicolls et al 2006). Specifically, Fejer et al (2008) showed that during equinox, for geomagnetically disturbed periods, the equatorial drifts ascribable to the magnetospheric dynamo are upward from about 07 to 23 LT, those due to the ionospheric dynamo are upward between 21 and 16 LT during equinox, with the amplitudes of daytime ones (between 07 and 16 LT) that are significantly lower than the nighttime ones (between 21 and 06 LT).…”
Section: Resultsmentioning
confidence: 99%
“…The prompt penetration/undershielding electric field (PPEF) of eastward polarity has largest amplitude in the evening sector (Fejer et al 2008), and its occurrence almost in-phase with the quiet time PRE can cause post-sunset plasma bubble development during a season of negligible or small PRE value, as June months in Brazil (Abdu et al 2003). A case of post-sunset bubble development due to an under-shielding electric field, in a bubble non-occurrence season in the Asian longitude sector, during the 10 November 2004 super storm, was presented by Li et al (2009).…”
Section: Variability Due To Penetration Electric Fieldsmentioning
confidence: 99%
“…The penetration efficiency of the PPEF can vary so that the ionospheric electric field can be as much as 5-10 % of the IEF (see, for example, Kelley and Retterer 2008;Huang et al 2010). The intensity and polarity of the penetration electric fields will depend also on large-scale conductivity gradients of the ionosphere so that the daytime eastward electric field extends into postsunset hours peaking near the time of the PRE, prior to its westward reversal by ~21 LT, and the night-side westward electric field peaking in the pre-sunrise hours prior to its eastward reversal by ~05-07 LT (Richmond et al 2003;Fejer et al 2008). The disturbance dynamo electric field (DDEF) arising from the auroral heating that sets off equator-ward thermospheric disturbance winds occurs with a time delay of several hours (from the storm development) (Richmond et al 2003), and it has the polarity local time dependence similar to that of the over-shielding electric field.…”
Section: Forcing Due To Solar and Magnetospheric Disturbancesmentioning
confidence: 99%
“…Conversely on the nightside this produces an excess westward electric field causing a downward flow of ions. This excess upward (downward) flow on the dayside (nightside) after a geomagnetic storm onset has been observed by radar (e.g., Kelley et al, 2003;Huang et al, 2005;Fejer et al, 2007) and satellite measurements (e.g., Fejer et al, 2008;Huang, 2008).…”
Section: Introductionmentioning
confidence: 99%